High-Performance Birefringence of Periodic Nanostructures in FTO Thin Film Fabricated by IR-UV Femtosecond Laser - Zhang, Fengzhuo; Chen, Long; Zhang, Yuchan; Jiang, Qilin; Feng, Donghai; Zhang, Shian; Jia, Tianqing; Sun, Zhenrong; Xu, Hongxing (Frontiers in Physics, 2022)
By using infrared to ultraviolet (IR-UV) femtosecond laser directing, periodic nanostructures were efficiently fabricated in F-doped Tin Oxide (FTO) film with a thickness of 650 nm. The morphology of nanostructures and duty cycle were studied in detail by changing the laser fluence and scanning speed, where three lasers with central wavelengths of 343 nm, 515 nm and 1030 nm were used in the experiments, respectively. The birefringence Δn reaches the maximum of 0.21, and the phase retardance is up to 135 nm when the FTO film was irradiated by 515 nm laser with a fluence of 23 mJ/cm2 at a scanning speed 0.01 mm/s. The morphology of nanostructures and the birefringence effects of FTO film prepared by femtosecond laser at the wavelength of 1030 and 343 nm were also studied. The phase retardance of the nanostrucutred FTO film are both much less than that fabricated by 515 nm laser because the thickness of nanoripples layer is smaller or the duty cycle of periodic nanoripples is smaller. Finally, a large-area FTO film with periodic nanostructures was fabricated efficiently by direct laser writing using 515 nm femtosecond laser focused via a cylindrical lens, and demonstrates the performance of a quarter-wave plate of 532 nm light.